2022
DOI: 10.3389/fphar.2022.934740
|View full text |Cite
|
Sign up to set email alerts
|

Maca (Lepidium meyenii Walp.) on semen quality parameters: A systematic review and meta-analysis

Abstract: Background: This study aimed to examine the evidence for the effect of Lepidium meyenii Walp. [Brassicaceae] (L. meyenii W.), known as maca, on improving semen quality.Methods: Nine databases were searched for randomized controlled trials (RCTs) that examined the parameters for improvements in semen quality, regardless of the type of L. meyenii W. The risk of bias (ROB) among the studies was evaluated according to the Cochrane ROB tool.Results: Five RCTs met all of the inclusion criteria. Three RCTs showed mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The use of this phytobooster was found to be significantly and reliably correlated with positive treatment outcomes for male sexual disorders in 7 out of 11 randomized placebo-controlled studies, multiple cohort studies, and pilot studies conducted between 2000 meyenii on several parameters of ejaculate quality in healthy men. Thus, more research is needed to determine the exact impact of Lepidium meyenii on the quality of ejaculates in both infertile and healthy men, as indicated by the data from meta-analyses (Lee et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The use of this phytobooster was found to be significantly and reliably correlated with positive treatment outcomes for male sexual disorders in 7 out of 11 randomized placebo-controlled studies, multiple cohort studies, and pilot studies conducted between 2000 meyenii on several parameters of ejaculate quality in healthy men. Thus, more research is needed to determine the exact impact of Lepidium meyenii on the quality of ejaculates in both infertile and healthy men, as indicated by the data from meta-analyses (Lee et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It concluded that the evidence was unclear and too scant to support its use. While the authors noted the absence of studies, one of the issues in making a proper assessment was the absence of defining maca colors within the individual studies to examine whether there was a targeted effect of one type of maca over another, which might be anticipated with black maca based on animal data [35]. 9.1.…”
Section: Black Macamentioning
confidence: 99%
“…The protocol was registered at reviewregistry 1346 [19]. The standard methods of performing systematic reviews were followed for this review.…”
Section: Registrationmentioning
confidence: 99%
“…Several in vivo studies have shown that maca can improve sexual behavior and enhance androgen-like effects in rats [14,15]. Systematic reviews have suggested that maca increases sperm count and motility and improves sexual function in humans [13,16,17].…”
Section: Introductionmentioning
confidence: 99%